Molecular identification of a ‘Candidatus Phytoplasma trifolii’ (16SrVI-D) strain associated with Scurfy pea (Cullen corylifolium) phyllody and witches’ broom in India - Tripathi, Savarni; Verma, Abhishek; Verma, Raj; Khar, Anil (Journal of Plant Protection Research, 2025)
Scurfy pea (Cullen corylifolium (L.) Medik.) plants exhibiting symptoms of phyllody and witches’ broom indicative of phytoplasma infection were observed in the research field of ICAR – Indian Agricultural Research Institute, Regional Station, Pune (Maharashtra, India). Phytoplasma presence in all symptomatic samples was confirmed through PCR and nested PCR assay using phytoplasma-specific primer pairs P1/P7 and R16F2n/R2. BLASTn analysis revealed that the amplicon sequence shares more than 99% identity with known strains of ‘Candidatus Phytoplasma trifolii’ sequences. Phylogenetic analysis further clustered the sequence of the phytoplasma strain within the ‘Ca. Phytoplasma’ species while virtual RFLP analysis assigned it to the 16SrVI-D subgroup. To the best of our knowledge, this is the first worldwide report of 16SrVI-D phytoplasma associated with phyllody and witches’ broom in C. corylifolium.